2005
DOI: 10.1111/j.1523-1755.2005.00434.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased levels of circulating endothelial cells in chronic periaortitis as a marker of active disease

Abstract: The presence of a high number of CECs in the active phase of chronic periaortitis and their normalization during inactive disease suggest that endothelial damage may play a role in the pathogenesis of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 32 publications
(37 reference statements)
0
12
0
2
Order By: Relevance
“…EPC are believed to be a distinct population from that of mature circulating endothelial cells (CEC), which are EC that may have detached from the endothelial vasculature after injury [23,24]. Although there are suggestions of a common ancestry for these two populations (reviewed in reference [25]), increased CEC number is viewed as a reflection of severe vascular damage [26] whereas increased EPC number is interpreted as an important index of vascular repair [27][28][29][30]. Unfortunately the ability to clearly distinguish various endothelial phenotypes in peripheral blood is limited and therefore ascribing a specific functional role to EPC in vivo may be premature.…”
Section: Endothelial Progenitor Cellsmentioning
confidence: 99%
“…EPC are believed to be a distinct population from that of mature circulating endothelial cells (CEC), which are EC that may have detached from the endothelial vasculature after injury [23,24]. Although there are suggestions of a common ancestry for these two populations (reviewed in reference [25]), increased CEC number is viewed as a reflection of severe vascular damage [26] whereas increased EPC number is interpreted as an important index of vascular repair [27][28][29][30]. Unfortunately the ability to clearly distinguish various endothelial phenotypes in peripheral blood is limited and therefore ascribing a specific functional role to EPC in vivo may be premature.…”
Section: Endothelial Progenitor Cellsmentioning
confidence: 99%
“…CEC exhibit no long-term proliferation potential and circulate in the peripheral blood. An increase in CEC number is viewed as a reflection of severe vascular damage [13]. Duda et al reported that CEC can be defined as a discrete population of cells expressing CD31 bright CD45 − CD34 dim CD1 33 − [14].…”
Section: Mature Circulating Endothelial Cells and Vascular Repairmentioning
confidence: 99%
“…In a recent study, Moroni et al [18] found that patients with CP had a significantly increased number of circulating endothelial cells (CECs) in comparison to healthy subjects, patients with diffuse ATS, and patients with renal insufficiency of variable degree and etiology. These data indicate that endothelial injury, as part of immune-mediated inflammatory vascular damage, may play a role in the pathogenesis of CP.…”
Section: Potential Role Of Atherosclerosis In Chronic Periaortitismentioning
confidence: 99%